Sushi party : kawaii sushi made easy! - Kawasumi, Ken (Tuttle Publishing, 2020)
"This book shows you the simple techniques used to make kawaii decorative sushi that will delight everyone who sees them! Renowned Japanese sushi chef Ken Kawasumi has assembled 55 super-cute sushi recipes... Each recipe has detailed step-by-step instructions with photographs showing the individual stages, assembly techniques and the finished dish. There is also a comprehensive guide to basic sushi rice preparation, rolling techniques and handling seafood safely. The glossary sorts the sushi creations by color, allowing you to easily plan your theme and color-coordinate your party."--